Myrsidea Waterston (Phthiraptera: Menoponidae) from tanagers (Passeriformes: Thraupidae), with descriptions of 18 new species - Price, Roger D.; Dalgleish, Robert C. (Zootaxa, 2006)
The four species of previously named Myrsidea from tanagers are redescribed. Eighteen new species are described and illustrated. They and their type hosts are Myrsidea cyanocephalae ex Thraupis cyanocephala (d’Orbigny and Lafresnaye), M. suttoni ex Euphonia jamaica (L.), M. tangarae ex Tangara mexicana (L.), M. icterocephalae ex Tangara icterocephala (Bonaparte), M. violaceae ex Euphonia violacea (L.), M. melanopis ex Schistochlamys melanopis (Latham), M. cayanae ex Tangara cayana (L.), M. ophthalmici ex Chlorospingus ophthalmicus (Du Bus), M. fuscicaudae ex Habia fuscicauda (Cabanis), M. zenae ex Spindalis zena (L.), M. rufi ex Tachyphonus rufus (Boddaert), M. phoenicii ex Tachyphonus phoenicius Swainson, M. diglossae ex Diglossa lafresnayii (Boissonneau), M. venustae ex Dacnis venusta Lawrence, M. ramphoceli ex Ramphocelus carbo (Pallas), M. surinami ex Tachyphonus surinamus (L.), M. spizae ex Chlorophanes spiza (L.), and M. mitrospingi ex Mitrospingus cassinii (Lawrence). Keys are provided for the identification of these 22 species.